Implementing Human Resource Management to Enhance Teacher Performance in Private Islamic Senior High Schools: Evidence from Ogan Komering Ulu Regency - Purnomo, Suryo Setio (Universitas Islam Negeri Raden Intan Lampung, 2026)
Human Resource Management (HRM) plays a strategic role in improving teacher performance, particularly in Islamic educational institutions that face complex managerial and contextual challenges. This study aims to analyze the implementation of human resource management in enhancing teacher performance and to identify the supporting and inhibiting factors influencing its effectiveness in private Madrasah Aliyah. Employing a descriptive qualitative approach, this research was conducted in three private Islamic senior high schools in Ogan Komering Ulu Regency, South Sumatra, Indonesia. Data were collected through in-depth interviews, participant observations, and document analysis, and were analyzed thematically to capture patterns of HRM practices and teacher performance dynamics. The findings reveal that HRM implementation in the studied madrasahs has been carried out through structured planning, competency-based teacher development, performance evaluation, and the optimization of institutional programs. Leadership of the madrasah principals, support from professional organizations, community involvement, and the availability of basic infrastructure emerged as key supporting factors. Conversely, limited teacher competencies, inadequate facilities, and weak coordination with external stakeholders were identified as major inhibiting factors. Despite these constraints, HRM practices have contributed positively to improving teacher discipline, instructional quality, and professional commitment. This study concludes that effective human resource management significantly enhances teacher performance in private Islamic senior high schools, although continuous capacity building and institutional support remain essential for sustainable improvement. The findings offer practical implications for educational leaders and policymakers in strengthening HRM strategies within Islamic education contexts.